Acute effects of static stretching on isokinetic thigh strength on modern dancers - Agopyan, A.; Tekin, D.; Unal, M.; Kurtel, H.; Turan, G.; Ersoz, A. (EDIZIONI MINERVA MEDICA, 2013)
Aim. The aim of this study was to examine the acute effects of static stretching in dominant leg flexor muscle groups on concentric isokinetic leg extension and flexion peak torque (PT), peak torque % body weight (PT %BW) and total work (TW) at 60, 180 and 300 degrees.s(-1) in stretched and non-stretched limbs of modern dancers. Methods. Twenty-six trained modern dancers volunteered in this study. On the first measurement, isokinetic tests were performed on dominant and non-dominant legs. On the second measurement, the dominant leg flexors were stretched using 3 unassisted and 1 assisted static stretching exercises (each 4x15 seconds; 10-second rest). After the stretching, isokinetic tests were repeated on both legs. Results. The results indicated a positive increase in strength in the stretched (PT %BW, TW) and non-stretched (PT, PT %BW, TW) limbs in flexion at 180 degrees s(-1) (P<0.05). We observed a positive increase (P<0.05) in the stretched limb (180 and 300 degrees.s(-1), TW; 300 degrees.s(-1), PT %BW) in extension whereas an acute decrease (P<0.05) was observed in both legs (60 degrees.s(-1), PT and PT %BW). Conclusion. Our findings indicated a possible positive effect of static stretching at high angular velocities on the strength production of isokinetic contraction in stretched and non-stretched muscles. However, due to its negative effect on the extensor muscle groups, we think using static stretching is required attention before maximal strength exercises.
Keywords: Muscle stretching exercise; Plyometric exercise; Postexercise hypotension; Dancing; MEAN POWER OUTPUT; PEAK TORQUE; SKELETAL-MUSCLE; PERFORMANCE; ELECTROMYOGRAPHY; DURATION; EXERCISE; SPEED; ANGLE; Sport Sciences